2005
DOI: 10.1163/1568568054089384
|View full text |Cite
|
Sign up to set email alerts
|

A continuously lit stimulus is perceived to be shorter than a flickering stimulus during a saccade

Abstract: When subjects made a saccade across a single-flashed dot, a flickering dot or a continuous dot, they perceived a dot, an array (phantom array), or a line (phantom line), respectively. We asked subjects to localize both endpoints of the phantom array or line and calculated the perceived lengths. Based on the findings of Matsumiya and Uchikawa (2001), we predicted that the apparent length of the phantom line would be larger than that of the phantom array. In Experiment 1 of the current study, contrary to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The reasons for this are unclear, though it may be related to their use of a flickering stimulus, as opposed to our continuously lit stimulus. Although a 500 Hz flicker such as the one used in their experiment is above the threshold for flicker-fusion, it can be differenti-ated from a continuously lit stimulus intra-saccadically, both by the appearance of a phantom array, in contrast to a smear (Hershberger, 1987), and by its greater perceived length (Noritake, Kazai, Terao, & Yagi, 2005). It is therefore possible that there is a difference in the way these two stimuli are processed extra-retinally.…”
Section: Discussionmentioning
confidence: 94%
“…The reasons for this are unclear, though it may be related to their use of a flickering stimulus, as opposed to our continuously lit stimulus. Although a 500 Hz flicker such as the one used in their experiment is above the threshold for flicker-fusion, it can be differenti-ated from a continuously lit stimulus intra-saccadically, both by the appearance of a phantom array, in contrast to a smear (Hershberger, 1987), and by its greater perceived length (Noritake, Kazai, Terao, & Yagi, 2005). It is therefore possible that there is a difference in the way these two stimuli are processed extra-retinally.…”
Section: Discussionmentioning
confidence: 94%
“…Veitch and McColl 7 compared visual performance and visual comfort under fluorescent lighting systems operated on magnetic (120 Hz, 43-98% flicker, 0.14-0.33 flicker index) and electronic (20 000 þ Hz, percent flicker and flicker index not reported) ballasts and found small differences in performance, but not comfort, between them. Noritake et al 8 found that the localisation of objects when making saccades was less accurate for a flickering stimulus (200 Hz, 100% flicker, 0.8 flicker index); it is possible that these misjudgements could contribute to discomfort over time, although this is speculation. In addition to the factors listed above, other factors can also impact the direct or indirect perception of flicker: 9 Duty cycle (defined as the percentage of time within a waveform that the light output exceeds 10% of the maximum output)…”
Section: Introductionmentioning
confidence: 99%